Histopathological investigation of tissues from chickens and pigeons infected with avian poxvirus in Diyala governorate - Faisal, Aisha; Al-Azzawi, Amer (Diyala Journal for Veterinary Sciences, 2023)
The virus of the genus Avipox virus, which is a member of the subfamily chordopoxvirinae in the family poxviridae, is the source of the viral disease known as avian pox, which can infect both domestic and wild birds. The two diseases that were seen were diphtheritic and cutaneous. The cutaneous form is distinguished by skin sores on the portions of the bird without feathers. The development of fibronecrotic, proliferative lesions on the mucous membranes of the respiratory and digestive systems distinguishes the diphtheritic form. This study's goal is to look into the pigeons' and chickens' histology avian pox lesions.From October 2022 to March 2023, the current study was carried out at Diyala University's College of Veterinary Medicine. Twenty tissue samples of pigeons (Columba livia domestica) and chicken (Gallus gallus) from Diyala Governorate's affected vents, eyes, wings, cere, and base of the beak were collected and processed for a histological analysis. The results showed that papules, pustules, or scabs made up the majority of the skin lesions in pigeons. However, in other instances, both single and many nodular growths as well as growths that resembled cauliflower were seen. The bird's eyes, beak, legs, vent, and toes all have these lesions. However, the head and combs were the most common locations for skin lesions in hens. The virus clearly altered the epidermal tissue of pigeon and chicken cutaneous lesions, as evidenced by the hyperplasia of stratified squamous cells with acanthosis and the severe inflammatory exudate containing heterophils, macrophages, and lymphocytes. The stratified squamous epithelium was found to be in a ballooning degeneration stage. The epithelial cells were puffy, round, and scattered widely. Massive eosinophilic inclusions, or Bollinger bodies, were seen in the cytoplasm of hyperplastic epithelial cells, as well as vacuolation, which was constantly present and recognized as ring-shaped eosinophilic intracytoplasmic inclusions. It was concluded that the avian pox virus resulted in distinct pathological alterations in the cutaneous areas, specifically affecting the epidermal tissues in pigeons and chickens.